Oss vänner emellan - En fallstudie av amerikanskt spionage på allierade - Matos,Mario (2015)
The media reports that began in June 2013 concerning US intelligence activities directed against the allies shocked many. It was found that longstanding alliance members conducted intelligence activities against each other. According to these reports, the US intelligence agencies (NSA and CIA) have been spying on Germany. This is a theory-consuming case study about espionage on allies, more specifically American espionage on Germany. The study addresses the question: How can we explain that the longstanding alliance members are conducting intelligence activities directed against one another? The results indicate that US intelligence agencies have engaged in intelligence activities directed against Germany. Furthermore, results indicate that the intelligence services have acted on their own initiative, without the American President being aware of the details of the intelligence activities.
Keywords: spionage; allierade; USA; Tyskland; underrättelsetjänst